Powering Incentive Compensation: How Utilities Pay for Performance. (March 2013) - Hall, Steven; McCord, Nora
Steven Hall & Partners recently completed a study of incentive compensation programs at 73 of the largest utility companies in the United States. Utility companies face unique challenges when designing incentive compensation programs, due to the greater number of stakeholders to whom they must be responsive, intense media scrutiny, stringent regulatory constraints and the need for regular public approval of rate cases. Although fixed compensation in the form of base salaries does represent a greater percentage of total compensation among utilities, this is not to say that utilities have ignored incentive-based compensation. In fact, utility companies pay for a broader range of performance than many other public companies. In addition to common performance metrics like earnings and shareholder returns, utilities also consider nonfinancial performance metrics such as safety and customer service, which serve as strong public demonstrations of a commitment to performance objectives shared by customers and shareholders alike.